2019
DOI: 10.1016/j.cell.2019.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sensing of Physiologic pH and Calcium by EFCAB9 Regulates Sperm Motility

Abstract: Highlights d Efcab9 encodes an evolutionarily conserved, sperm-specific EF-hand domain protein d Efcab9-deficient mice have sperm motility defects and compromised male fertility d EFCAB9 senses both pH and Ca 2+ helping regulate flagellar CatSper channel activity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
287
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(303 citation statements)
references
References 61 publications
12
287
2
2
Order By: Relevance
“…In most sperm species, [Ca 2+ ] i is set by the voltage-and alkaline-activated CatSper Ca 2+ channel (Quill et al, 2001;Ren et al, 2001;Kirichok et al, 2006;Lishko et al, 2010;Lishko et al, 2011;Strü nker et al, 2011;Loux et al, 2013;Seifert et al, 2015). Mammalian CatSper comprises four homologous pore-forming subunits (CatSper 1-4) (e.g., Navarro et al, 2008) and at least six auxiliary subunits (CatSper b, c, d, ɛ, f, and Efcab9) (Liu et al, 2007;Wang et al, 2009;Chung et al, 2011Chung et al, , 2017Hwang et al, 2019). The CatSper-channel complex is organized as quadrilateral threads along the flagellum; the CatSper threads encompass several other proteins, including Ca 2+ -binding proteins and protein kinases, forming local Ca 2+ -signaling domains near the membrane surface (Chung et al, 2014(Chung et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In most sperm species, [Ca 2+ ] i is set by the voltage-and alkaline-activated CatSper Ca 2+ channel (Quill et al, 2001;Ren et al, 2001;Kirichok et al, 2006;Lishko et al, 2010;Lishko et al, 2011;Strü nker et al, 2011;Loux et al, 2013;Seifert et al, 2015). Mammalian CatSper comprises four homologous pore-forming subunits (CatSper 1-4) (e.g., Navarro et al, 2008) and at least six auxiliary subunits (CatSper b, c, d, ɛ, f, and Efcab9) (Liu et al, 2007;Wang et al, 2009;Chung et al, 2011Chung et al, , 2017Hwang et al, 2019). The CatSper-channel complex is organized as quadrilateral threads along the flagellum; the CatSper threads encompass several other proteins, including Ca 2+ -binding proteins and protein kinases, forming local Ca 2+ -signaling domains near the membrane surface (Chung et al, 2014(Chung et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Catsper channels regulation, progesterone activates Catsper channels in human testicular and epididymal spermatozoa by binding to the sperm-membrane receptor; α/β hydrolase domain-containing protein 2 (ABHD2) which acts removing Catsper inhibitors to allow the channel to open [56][57][58][59][60]. However, it has been described in mouse spermatozoa that Catsper channels are activated by an increase in intracellular pH [61,62], and further they do not react to progesterone in vitro [56]; a situation similar to what our group recently reported for pig spermatozoa [36]. In the mouse, ABHD2 does not seem essential for male fertility [56], an assumption which would be backed up by our results, considering that ABDH2 was downregulated in the pig UTJ and Isth after mating compared to the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its crucial roles in mammalian sperm function, the activation mechanism of CatSper has drawn intensive attention. Besides intrinsic pH and voltage sensitivities (19, 20, 21, 30, 31), CatSper is able to be activated by many physiological and environmental factors (27, 32). However, almost all previous studies suggested that intracellular signaling pathways are not involved in the activation of CatSper by extracellular signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Because CatSper is present in species ranging from lower invertebrates to higher mammals and plays crucial role in sperm function regulation (19, 29), the activation mechanism of CatSper has drawn intensive attention. Besides intrinsic pH and voltage sensitivities (19, 20, 21, 30, 31), CatSper can be activated by a variety of physiological and environmental factors (27, 32), which had all been proposed to activate CatSper directly, leading to the idea that CatSper is a poly-modal sensor (27). Interestingly, recently progesterone has been shown to increase CatSper current by activating orphan enzyme alpha/beta hydrolase domain containing protein 2 (ABHD2) to remove an endogenous inhibitory effect of endocannabinoid 2-arachidonoylglycerol (2-AG) on CatSper (33).…”
Section: Introductionmentioning
confidence: 99%